Transitional journeys into, and through medical education for First-in-Family (FiF) students: a qualitative interview study - Bassett, Andrew Mark (BMC Med Educ, 2018)
BACKGROUND: There has been much interest in the transitions along the medical education continuum. However, little is known about how students from non-traditional backgrounds experience both the move to, and through Medical School, and their ambitions post-graduation. This research sought to understand the transitional journey into, and through undergraduate medical education, and future career aspirations for first-in-family (FiF) medical students. METHODS: Based on a interpretivist epistemological perspective, 20 FiF students from one English Medical School participated in semi-structured interviews. Participants were identified according to purposive inclusion criteria and were contacted by email via the student association at the Medical School and academic year leaders. The team approach to the thematic analysis enhanced the findings credibility. This research was part of an international collaboration. RESULTS: In the first transition, ‘The Road to Medical School’, a passion for science with an interest in people was a motivator to study medicine. Participants’ parents’ shared the elation of acceptance into Medical School, however, the support from school/college teachers was a mixed experience. In ‘The Medical School Journey’ transition, knowledge about the medical curriculum was variable. ‘Fitting’ in at Medical School was a problem for some, but studying for an elite degree elevated social status for many study participants. A source of support derived from senior medical student peers, but a medical degree could sacrifice students’ own health. In the final transition, ‘Future Plans’, a medical career was perceived to have intrinsic value. Clarity about future aspirations was related to clinical experience. For some, career trajectories were related to a work-life balance and future NHS working conditions for Junior Doctors. CONCLUSIONS: The transitions highlighted in this article have important implications for those educators interested in a life cycle approach to widening participation in medical education. Future research should explore the post-graduation transitions for doctors from first-in-family University backgrounds.